Emerging Endoscopic and Photodynamic Techniques for Bladder Cancer Detection and Surveillance - Prashant Patel; Richard T. Bryan; D. Michael A. Wallace (The Scientific World Journal)
This review provides an overview of emerging techniques, namely, photodynamic diagnosis (PDD), narrow band imaging (NBI), Raman spectroscopy, optical coherence tomography, virtual cystoscopy, and endoscopic microscopy for its use in the diagnosis and surveillance of bladder cancer. The technology, clinical evidence and future applications of these approaches are discussed with particular emphasis on PDD and NBI. These approaches show promise to optimise cystoscopy and transurethral resection of bladder tumours.